2009
DOI: 10.1007/s12094-009-0414-y
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for occipital condyle metastasis

Abstract: We present a 45 year old female with right occipital condylar metastases who was treated at William Beaumont Hospital in the Gamma Knife Unit. Clinical results at 17 months follow-up and MRI are exposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…8 In our literature review, we found 1 case report of a patient with an occipital condyle metastasis treated with GKS, which resulted in a reduction in tumor size without evidence of disease recurrence after a prescribed peripheral marginal dose of 8 Gy (with a maximal dose of 17.77 Gy). 12 In our study, however, destruction of both tables of the skull was typical and the underlying dura was often involved. Therefore, considering the adjacent brain parenchyma, we applied our traditional brain metastasis dosing guidelines to maximize tumor control.…”
Section: Discussioncontrasting
confidence: 50%
“…8 In our literature review, we found 1 case report of a patient with an occipital condyle metastasis treated with GKS, which resulted in a reduction in tumor size without evidence of disease recurrence after a prescribed peripheral marginal dose of 8 Gy (with a maximal dose of 17.77 Gy). 12 In our study, however, destruction of both tables of the skull was typical and the underlying dura was often involved. Therefore, considering the adjacent brain parenchyma, we applied our traditional brain metastasis dosing guidelines to maximize tumor control.…”
Section: Discussioncontrasting
confidence: 50%
“…5,20 Though evidence specific to the CVJ is limited, small case series have yielded promising results. 9,16,21 SRS at the CVJ is not without challenges, given the proximity of adjacent neurocritical structures including the brainstem, upper cervical spinal, and lower cranial nerves. We present the largest patient series, to our knowledge, of SRS for CVJ metastasis and demonstrate the role of this treatment modality in preserving spinal stability and alleviating pain.…”
mentioning
confidence: 99%